2003
DOI: 10.1002/bies.10298
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis: Which part of “NO” do we understand?

Abstract: SummaryA recent paper by Nisoli et al. (1) provides the first evidence that elevated levels of nitric oxide (NO) stimulate mitochondrial biogenesis in a number of cell lines via a soluble guanylate-cyclase-dependent signaling pathway that activates PGC1a (peroxisome proliferator-activated receptor g coactivator-1a), a master regulator of mitochondrial content. These results raise intriguing possibilities for a role of NO in modulating mitochondrial content in response to physiological stimuli such as exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…It has been reported that the mass of mammalian mitochondria is increased in cells that have defects in the respiratory chain (74), adipose tissue upon cold shock (75) or exercise-conditioned skeletal muscle (1), suggesting that the mitochondria has an autoregulatory system to adjust its function for cellular demand, to keep ATP levels constant (76). Although transcription factors and coactivators such as Tfam, NRF1, NRF2, SP1, YY1, CREB, MEF2 and PGC-1 alpha are reported to be involved in the transcriptional induction of genes responsible for mitochondrial function and biogenesis, the mitochondrial biosynthetic program appears to be regulated by multiple transcriptional regulatory pathways, including the mitochondrial retrograde signaling and mitochondrial unfolded protein response.…”
Section: Mitochondrial Retrograde Signalingmentioning
confidence: 99%
“…It has been reported that the mass of mammalian mitochondria is increased in cells that have defects in the respiratory chain (74), adipose tissue upon cold shock (75) or exercise-conditioned skeletal muscle (1), suggesting that the mitochondria has an autoregulatory system to adjust its function for cellular demand, to keep ATP levels constant (76). Although transcription factors and coactivators such as Tfam, NRF1, NRF2, SP1, YY1, CREB, MEF2 and PGC-1 alpha are reported to be involved in the transcriptional induction of genes responsible for mitochondrial function and biogenesis, the mitochondrial biosynthetic program appears to be regulated by multiple transcriptional regulatory pathways, including the mitochondrial retrograde signaling and mitochondrial unfolded protein response.…”
Section: Mitochondrial Retrograde Signalingmentioning
confidence: 99%
“…These conditions manifest themselves in pathologies associated with tissues strictly dependent on proper mitochondrial function, such as nerve and muscle tissues (1)(2)(3). There is a direct correlation between energy demand and mitochondrial abundance, pointing to sophisticated regulatory mechanisms that control mitochondrial biogenesis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial (mt) function is emerging as an important contributor to the risk of diabetes (19,23,25) and other diseases related to aging (24,35). Transcription factors regulating the formation and activity of fat cells (6) are also regulators of mitochondrial function (14). Drugs used for treating AIDS that result in mtDNA depletion (due to inhibition of the mtDNA DNA polymerase) affect adipocyte differentiation both in vivo (22) and in tissue culture.…”
mentioning
confidence: 99%